Law Enforcement Perspectives on Sex Offender Registration and Notification: Effectiveness, Challenges, and Policy Priorities - Harris, Andrew J. R. (Criminal justice policy review, 2018)
Since the 1990s, sex offender registration and notification (SORN) has assumed a prominent place on state and federal crime control agendas in the United States. Although researchers have examined many aspects of SORN policies and systems, relatively little is known about how SORN is used, perceived, and experienced by law enforcement professionals in the context of their work. This article presents findings from a mixed-method study, consisting of face-to-face interviews and a national online survey of police and sheriff agencies. We examined law enforcement views on SORN’s general functions and efficacy, barriers to SORN effectiveness, and recommendations for SORN-related policy. Results highlight the challenges associated with SORN’s various functions as a law enforcement information tool, as an offender monitoring mechanism, and as a conduit of public information. They also indicate differences between the perspectives of agency leadership and those on the front lines of registry enforcement and management, as well as a range of concerns associated with the reliability and utility of registry information, inter-system communication, registrant homelessness and transience, and the public’s capacity to understand registry information. Implications for policy reform and for SORN-related research are discussed.